2009
DOI: 10.1002/ajpa.21150
|View full text |Cite
|
Sign up to set email alerts
|

Spouse selection by health status and physical traits. Sardinia, 1856–1925

Abstract: Military medical information and data from civil registers of death and marriage have been used to study the role of physical characteristics and health conditions in explaining access to marriage for the male population of Alghero, a small city located in Sardinia Island (Italy), at the turn of 19th century. Literature data about contemporary populations have already demonstrated the influence of somatic traits in the mate choice. The results presented here show that men with low height and poor health status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Facially more attractive and taller men more frequently engaged in marriage, and in turn, married men had higher reproductive success than unmarried men, corroborating and extending previous research (Pawlowski et al 2000;Nettle 2002;Jokela 2009;Manfredini et al 2010). Although Prokop et al (2010) did not find any associations between reproductive success and facial attractiveness, we suggest that this could be due to either their using photographs of older men for rating attractiveness (mean age of their participants was 47.7 years) as well as investigating only married men having at least one child.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Facially more attractive and taller men more frequently engaged in marriage, and in turn, married men had higher reproductive success than unmarried men, corroborating and extending previous research (Pawlowski et al 2000;Nettle 2002;Jokela 2009;Manfredini et al 2010). Although Prokop et al (2010) did not find any associations between reproductive success and facial attractiveness, we suggest that this could be due to either their using photographs of older men for rating attractiveness (mean age of their participants was 47.7 years) as well as investigating only married men having at least one child.…”
Section: Discussionsupporting
confidence: 85%
“…Tall men are more likely to marry (Manfredini et al 2010) and are more attractive to females (Hensley 1994;Pierce 1996;Mueller and Mazur 2001;Manfredini et al 2010), which is supported by high response rates of females to male advertisements published in newspapers (Pawlowski and Koziel 2002;Koziel and Pawlowski 2003). In addition, some data indicate that more attractive women have on average taller husbands (Pawlowski et al 2008).…”
Section: Introductionmentioning
confidence: 83%
“…In addition to the difficulties in obtaining reliable data on the health and somatic traits of past populations, it is widely held that, in the past, marriage choices were dominated not only by social and religious norms but also by family strategy (Derosas 2003). Our previous research on the male population of Alghero, Sardinia, at the turn of the 19 th century (Manfredini, Breschi, and Mazzoni 2010) provides evidence to support the thesis that physical characteristics also played a very important role in a marriage system that was governed by family rather than individual choice. We also found that state of health represented a decisive element in the marriage strategies of the community's wealthiest families.…”
Section: Introductionmentioning
confidence: 74%
“…Not only were they more likely to die in early adulthood (Breschi et al 2008a), but they were also less likely to marry before the age of 40 (Manfredini, Breschi, and Mazzoni 2010). Here we have taken this research one step further by investigating whether these factors influenced not only the quantitative, but also the qualitative aspects of marriage.…”
Section: Conclusive Remarksmentioning
confidence: 91%
See 1 more Smart Citation